APPLICATION OF GRAPHIC EDITORS IN THE DESIGN OF INDUSTRIAL AND PUBLIC BUILDINGS - SHOFUL, IGOR; SOKOLOVSKA, OLENA; VALEVSKA, LIUDMYLA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article considers the role and importance of graphic editors in modern design of industrial and public buildings. The main software products used in architectural and engineering design are analyzed, in particular AutoCAD, Revit, ArchiCAD, SketchUp and others. Particular attention is paid to the advantages of using graphic editors, such as increasing the accuracy of drawings, automating design solutions, reducing the time for documentation execution and the possibility of three-dimensional modeling. Practical examples of the use of such programs in the design of load-bearing structures, communications, and the internal space of buildings are described. Current trends in digital transformation in the construction industry and the prospects for the development of BIM technologies are highlighted. Mastering the package is possible with the study of graphic programs CAD (computer-aided design system), AutoCAD, BIM technologies (information model of buildings and structures), nanoCAD SPDB (design documentation system for construction). The practical significance of the work done is that the results can be used in the execution of multi-color images (photographs), the construction of drawings, graphs, images with clear contours. These exercises, related to the definition of the smallest element, have not lost their relevance today. In order to instill interest in the future specialty in the classroom, students prepare information about metal, reinforced concrete, wooden structures, where each type has its own advantages and disadvantages compared to other products and materials. Their detailed practical application is given. The construction industry, in which there are strict requirements, state regulations, rules during the organization and performance of work, the use of computer technology is a prerequisite in the construction contract market.
Keywords: computer design; construction products; foundations; columns; trusses; wooden structures